2015
DOI: 10.1074/jbc.m114.629899
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Menin Regulates Bone Mass in Vivo

Abstract: Background: Constitutive homozygous Men1Ϫ/Ϫ mice at mid-gestation are small with craniofacial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…Also, knockout of Men1 in the liver (using albumin promoter/ALB-Cre), a tissue not targeted in MEN1, does not lead to tumors in the liver despite the complete loss of Men1 (Scacheri, et al 2004). Other mouse models with knockout of Men1 in pancreatic endocrine cell lineages, bone cells, and intestinal cells have also helped to gain insight into the physiological actions of menin (Bonnavion, et al 2015; Kanazawa, et al 2015; Liu, et al 2017; Sundaresan, et al 2016; Veniaminova, et al 2012). These elegant studies in genetically engineered mouse models show that menin may function as a cell-type-specific tumor suppressor, and that its action is only required in MEN1-associated target tissues to prevent tumorigenesis.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Also, knockout of Men1 in the liver (using albumin promoter/ALB-Cre), a tissue not targeted in MEN1, does not lead to tumors in the liver despite the complete loss of Men1 (Scacheri, et al 2004). Other mouse models with knockout of Men1 in pancreatic endocrine cell lineages, bone cells, and intestinal cells have also helped to gain insight into the physiological actions of menin (Bonnavion, et al 2015; Kanazawa, et al 2015; Liu, et al 2017; Sundaresan, et al 2016; Veniaminova, et al 2012). These elegant studies in genetically engineered mouse models show that menin may function as a cell-type-specific tumor suppressor, and that its action is only required in MEN1-associated target tissues to prevent tumorigenesis.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…7 In vitro studies in cell lines and primary osteoblasts derived from 6-month-old mice showed that menin promotes early osteoblast differentiation in committed cells. Knockdown of Men1 with antisense oligonucleotides lead to enhanced BMP2 signaling 8, 9, 10 and to facilitated inhibition of the late stage of osteoblast differentiation by potentiating TGF β -dependent Smad3 signaling.…”
mentioning
confidence: 99%
“…11, 12 Accordingly, reduced bone mass and reduced bone formation due to decreased osteoblast proliferation and differentiation and enhanced apoptosis have been reported using aged osteocalcin-cre mice crossed to Men1 floxed mice that leads to a conditional deletion of menin in the late stage of differentiated osteoblasts. 7 On the other hand, aged osteoblast-specific menin transgenic mice were found to display increased bone mass. 7 However, whether Men1 plays a role in bone cells to control bone integrity in young or middle-aged mice is completely unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MEN1 commonly develop bone disease with osteoporosis thought secondary to the hyperparathyroidism (56) (57). However, recent studies show that menin has important effects in bone particularly in regulating osteoblast activity which plays a key role in bone deveopment, remodeling and maintenance (58). Some MEN1 patients require multiple re-operations to control the recurrent or persistent hyperparathyroidism and reoperation can be difficult and associated with increased morbidity.…”
Section: Multiple Endocrine Neoplasia Type 1 (Men-1)mentioning
confidence: 99%